Effect Interaction of Gibberellic Acid and Urea Fertilizer on some Growth Characteristic of Fenugreek Plant (Trigonella foenum-graecum L.) - Yaseen, S. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A biological experiment was conducted to study the effect of different concentrations of gibberellic acid and urea fertilizer and their interactions in some characteristic related to green growth of fenugreek plant (Trigonella foenum-graecum L.) in the green house of Department of Biology in College of Education (IbnÂalÂHaitham)/Baghdad University for the growth season (2008Â2009) in pots of (5 kgm) soil per pot, and four concentrations of gibberellic acid were used, they are (0,25,50,100) ppm, these concentrations were sprayed after the perfection of  the  fourth leaf for the plant. Moreover, three levels of urea fertilizer were used, they were (0.25, 0.50, 1.00) gm/pot. These concentrations were added as two pushes, the first was added before agriculture and the second was added after (45) days of agriculture. The experiment was performed according to complete random design (CRD) and three repeated as the experiment has included (36) pots.  The results represent that the concentrations (25,50) ppm of gibberellic acid and (0.50, 1.00) gm/pot of urea fertilizer level lead to significant increasing of characteristics associated with plant height and dry weight of fenugreek plant, while the concentration of gibberellic acid (25 ppm) and urea fertilizer level at (0.50, 1.00) gm/pot give a significant increase of characteristics related to absolute growth mean, relative growth mean and number of branches related to fenugreek plant.